Concentración de fósforo, nitrógeno y carbono en suelo del Chaco semiárido con diferentes usos - Cespedes Flores, Flora Elizabet; Rey Montoya, Tania Soledad; Monaco, Ingrid Patricia; Fernandez Lopez, Carolina (Sociedad Argentina de Agroecología, 2022)
Poster